Implementing High-Quality Retroperitoneal Lymph Node Dissection for Testicular Cancer at an Australian Tertiary Hospital: Challenging the Centralisation Paradigm in High-Need Areas - Satasivam P; Alwis S; Sundaralingam S; Niall O (Research and Reports in Urology)
Prassannah Satasivam,1,2 Samith Alwis,1 Sudheshan Sundaralingam,2 Owen Niall2 1Department of Medicine, The University of Melbourne, Parkville, VIC, Australia; 2Department of Urology, Northern Health, Epping, VIC, AustraliaCorrespondence: Prassannah Satasivam, Northern Hospital Department of Urology, 185 Cooper St, Epping, VIC, 3076, Australia, Email prassannah.satasivam@nh.org.auBackground: Retroperitoneal lymph node dissection (RPLND) plays an integral role in the curative management of metastatic testicular cancer. As a major surgery, RPLND poses a risk of significant complications, particularly in the post-chemotherapy (PC-RPLND) setting. We assessed the safety of introducing RPLND as a new service at an Australian tertiary hospital.Methods: A strict protocol prioritising appropriate case selection, multidisciplinary surgical expertise and ready access to intensive care facilities was implemented to introduce RPLND. Prospective data was collected on patients who underwent PC-RPLND between October 2020 and October 2022 at the Northern Hospital in Melbourne. Primary and secondary endpoints were 30-day postoperative Clavien-Dindo (CD) classification complication rate and perioperative quality measures, respectively.Results: Six patients (mean age 28.7 ± 4.3 years) underwent bilateral template open PC-RPLND. Median node count was 17 (IQR = 16) with metastatic germ cell tumour identified in all patients on histopathology. Median length of stay was 6 days (IQR = 3) with 1 day in intensive care. No blood transfusions were required, and no 30-day CD complications were encountered. Median follow-up was 22 months (IQR = 21) with no recurrences or significant delayed complications.Conclusion: Following a strict protocol, RPLND has been safely introduced as a new service at our tertiary institution. Perioperative quality endpoints match those of high-volume international centres.Keywords: testicular cancer, retroperitoneal lymph node dissection, postoperative complications